Opowieść transmedialna jako przykład kreacyjnych możliwości fandomu - CZOPEK, JAKUB (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Jakub Czopek, Opowieść transmedialna jako przykład kreacyjnych możliwości fandomu [Transmedia story as an example of creative possibilities of fandom]. Interdyscyplinarne Konteksty Pedagogiki Specjalnej, nr 23, Poznań 2018. Pp. 191-202. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.23.11 The subject of the article is the creative activity of fan communities (fandom), with particular emphasis on the transmedia storytelling, i.e. the story told simultaneously within various media. The development of the Internet in the Web 2.0 formula has opened a number of possibilities for the creation of fandoms centered around a particular series, movies, books or games. The main manifestations of the activity of these groups can be reduced on the one hand to analyzing and commenting on a given text of culture, and on the other hand, to develop it, by adding new stories, often using other medium than the one originally used.